What remains of the Cambridge critique of capital theory, if reswitching and reverse capital deepening are empirically rare and theoretically unlikely? - Bertram Schefold (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The paper summarises the main results of the Cambridge controversy on capital theory and discusses its actual relevance. The paradoxes that had first been regarded as most relevant (reswitching and reverse capital deepening) have turned out to be empirically rare, and this can be explained theoretically, but both neoclassical and anti-neoclassical Wicksell effects are ubiquitous. The number of efficient techniques that turn up on the envelope of the wage curves of a spectrum of techniques can be shown to be quite small both empirically and theoretically, which constitutes a new critique. It has implications for employment policies.
Keywords: B24; C62; C67; D57; 330; capital theory; production function; reswitching; Sraffa; employment